Genetic Analysis of Small Well-differentiated Pancreatic Neuroendocrine Tumors Identifies Subgroups With Differing Risks of Liver Metastases - Pea, Antonio (Ann Surg, 2018)
OBJECTIVE: The aim of this study was to investigate the key molecular alterations in small primary pancreatic neuroendocrine tumors (PanNETs) associated with the development of liver metastases. BACKGROUND: Well-differentiated PanNETs with small size are typically indolent; however, a limited subset metastasize to the liver. METHODS: A total of 87 small primary PanNETs (<3cm), including 32 metastatic cases and 55 nonmetastatic cases after a 5-year follow-up, were immunolabeled for DAXX/ATRX and analyzed for alternative lengthening of telomeres (ALT) by Fluorescence In Situ Hybridization. A subset of these cases, 24 that metastasized and 24 that did not metastasize, were assessed by targeted next-generation sequencing and whole-genome copy number variation. RESULTS: In the entire cohort, high Ki-67 (OR 1.369; 95% CI 1.121–1.673; P = 0.002), N-stage (OR 4.568; 95%CI 1.458–14.312; P = 0.009), and ALT-positivity (OR 3.486;95%CI 1.093–11.115; P = 0.035) were independently associated with liver metastases. In the subset assessed by next-generation sequencing and copy number variation analysis, 3 molecular subtypes with differing risks of liver metastases were identified.Group 1 (n = 15; 73%metastasized) was characterized by recurrent chromosomal gains, CN-LOH, DAXX mutations, and ALT-positivity.Group 2 (n = 19; 42% metastasized, including 5 G1 tumors) was characterized by limited copy number alterations and mutations. Group 3 (n = 14; 35% metastasized) were defined by chromosome 11 loss. CONCLUSIONS: We identified genomic patterns of small PanNETs associated with a different risk for liver metastases. Molecular alterations, such as DAXX mutations, chromosomal gains, and ALT, are associated with an increased risk of metastasis in small PanNETs. Therefore, targeted sequencing and/or AsLT analysis may help in the clinical decisions for these small PanNETs.